A legal analysis on the legislative process in enacting Islamic law in Malaysia / Afiq Zainal Abidin … [et al.] - Zainal Abidin, Afiq; Abdul Muti, Abdul Hadi; Ahmad Gholib, Nur Sabrina; Mohd Zain, Siti Nurfirziatul (Faculty of Law, 2012)
This project paper will be focusing on the problem of enacting Islamic Law in Malaysia. The Muslim population comprises up to 60% of the Malaysian citizen. One would think that being the majority then it should be easy to enact Islamic Law; however the situation would be different. Even though the majority of Malaysian population is Muslim, there are many obstacles that need to be faced in order to enact Islamic Law. This is due to the fact that a number of statutes which had failed while some of them are still pending to be passed at the Parliamentary stage and State Legislative Assembly raises the question on the practicality of current legislative process in enacting Islamic law in Malaysia. One of the conclusions that can be made in order to solve this issue is by effectively administered among the Muslim and without the interference by those who are incompetent in the field of Islamic Law. This project paper will analyses the weaknesses of the current legislative process and to further improve it by suggesting a few methods to overcome the problems of enacting Islamic Law.